THE MAIN METHODS OF ENSURING THE REGULARITY OF THE INTERESTS OF THE TEENAGE TAEKWONDO PLAYERS IN TRAINING - Polatov L. A.; Razzakova Mushtari (Journals Park Publishing, 2023)
In this article, I explained about the methods used to make teenagers who practice Taekwondo WT more interested in training processes. These methods are scientifically based and determined by experienced experts. If teenage taekwondo players are trained based on these methods, their interest in regular training will increase. In this process, the athlete must have the will and desire. It is not an exaggeration to say that this situation, that is, the athlete's desire to move forward, ensures that he regularly participates in any difficult and strenuous training process.
Keywords: Taekwondo, training methods, modern equipment, potential, motivation, environment, imagination, sport, human will, need, behavior, character, teacher, friend.